Effect of ximenynic acid on cell cycle arrest and apoptosis and COX-1 in HepG2 cells - Cai, F.; Li, J.; Liu, Yandi; Zhang, Z.; Hettiarachchi, Dhanushka; Li, D. (Spandidos Publications, 2016)
Ximenynic acid is a conjugated enyne fatty acid, which is currently of interest due to its anti-inflammatory activity. Due to the association between inflammation and cancer, the present study was designed to investigate the anti-cancer activity of ximenynic acid in the HepG2 human hepatoma cell line and the underlying mechanisms. The current study demonstrated the anti-proliferation and pro-apoptosis activities of ximenynic acid by cell viability assay and flow cytometry analysis. The expression of anti-apoptosis protein silent information regulator T1 (SIRT1) was significantly suppressed by ximenynic acid. Furthermore, ximenynic acid blocked G1/S phase transition by inhibiting the protein expression of the cell cycle-associated protein general control of amino acid synthesis yeast homolog like 2 (GCN5L2), and the mRNA expression of cyclin D3 and cyclin E1. Furthermore, ximenynic acid suppressed the expression of angiogenesis-associated genes, including vascular endothelial growth factor (VEGF)-B and VEGF-C. Finally, ximenynic acid significantly inhibited the expression of cyclooxygenase-1 (COX-1) mRNA and protein, however COX-2 expression was not reduced. The results of the present study suggested that ximenynic acid may inhibit growth of HepG2 cells by selective inhibition of COX-1 expression, which leads to cell cycle arrest, and alters the apoptosis pathway and expression of angiogenic factors. The current study aimed to investigate whether ximenynic acid might be developed as novel anticancer agent.